Study of the Effect of Bioplasticizer Type of Epoxy Used Cooking Oil on the Mechanical Properties of Rubber Vulcanizate - Andri Saputra; Pani Satwikanitya; Muh Wahyu Sya’bani; Mertza Fitra Agustian (Universitas Jayabaya, 2023)
The high volume of used cooking oil is one of the biggest obstacles. Unsaturated fatty acids in waste cooking oil have the potential as a raw material for producing plasticizer of epoxy oil. The development of renewable plasticizers based on natural materials to replace petroleum plasticizers has become the concern of many researchers due to the issue of depletion of petroleum raw materials, environmental problems, and health issues caused by petroleum plasticizers. This research aims to study the effect of different types of epoxy used cooking oil plasticizers on the mechanical properties of rubber vulcanizates. Used cooking oil that still contains unsaturated fatty acids was epoxidized by reflux method at 60oC using n-hexane solvent, glacial acetic acid catalyst and IR-120 amberlite resin, and oxygen donor hydrogen peroxide for 4 hours (MJE4), 6 hours (MJE6), and 8 hours (MJE8). The epoxy used cooking oil was characterized for oxirane number using the titration method. The epoxy cooking oil plasticizer was applied to the rubber compound and the mechanical properties of the rubber vulcanizate were tested. The analysis showed that MJE8 was the epoxy cooking oil with the highest oxirane number of 2.42% with a relative oxirane conversion of 84.92%. Epoxy cooking oil that has a higher oxirane content can increase the hardness and abrasion index, and reduce the tensile strength, elongation at break, and tear strength of rubber vulcanizates. The use of MJE8 produced rubber vulcanizates with higher elasticity properties, such as tensile strength (19.1 N/mm2), elongation at break (792.3%), and tear strength (26 N/mm). Meanwhile, MJE4 produced rubber vulcanizates with higher hardness and abrasion index with values of 68.7 HA and 90.8%, respectively.